2021
DOI: 10.1038/s41598-020-80736-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postoperative corticosteroids on surgical outcome and aqueous autotaxin following combined cataract and microhook ab interno trabeculotomy

Abstract: To evaluate the effect of postoperative corticosteroids on surgical outcome and autotaxin (ATX) levels after microhook ab interno trabeculotomy combined with cataract surgery (μLOT-CS), prospective, consecutive non-randomized case series comparing outcomes of 30 eyes with primary open angle glaucoma was performed. The aqueous ATX, intraocular pressure (IOP) and glaucoma medications were monitored for 3 months postoperatively. An in-vivo mouse μLOT model was generated. In vitro, ATX and fibrotic changes induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Excessive prostaglandin release that is a potent mediator of the inflammatory cascade causes breakdown of the bloodaqueous barrier, resulting in clinical symptoms such as pain, hyperemia, light sensitivity, and vision-threatening CME. 12,13 Prolonged inflammation leads to patient discomfort and delayed recovery and increases the risk of complications including increased IOP, posterior synechia, uveitis, secondary glaucoma, and posterior capsular opacification. 14 Prophylactic anti-inflammatory regimens vary widely among clinicians but mainly involve the perioperative use of corticosteroids and NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive prostaglandin release that is a potent mediator of the inflammatory cascade causes breakdown of the bloodaqueous barrier, resulting in clinical symptoms such as pain, hyperemia, light sensitivity, and vision-threatening CME. 12,13 Prolonged inflammation leads to patient discomfort and delayed recovery and increases the risk of complications including increased IOP, posterior synechia, uveitis, secondary glaucoma, and posterior capsular opacification. 14 Prophylactic anti-inflammatory regimens vary widely among clinicians but mainly involve the perioperative use of corticosteroids and NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 NSAIDs have been found to with steroids. 5,12,[17][18][19] In addition to blocking the inflammatory cascade, NSAIDs play an important role in preventing miosis during surgery, improving visualization, reducing intraoperative manipulation, and decreasing the risk of complications that may occur due to poor dilation. 20,21 Several prospective and retrospective clinical studies demonstrated that the combined use of postoperative NSAIDs and steroids is superior to either topical treatment alone in controlling pain and inflammation and reducing the risk for postoperative CME.…”
Section: Discussionmentioning
confidence: 99%
“…ATX levels in the AH have been positively correlated to postoperative corticosteroid use after microhook ab interno trabeculotomy for POAG. 136 Trabeculotomy is a procedure which involves cleaving the TM and inner wall of SC to reduce resistance to AH outflow in glaucoma patients. 136 Post-operative corticosteroids are associated with IOP spikes, 137 and therefore their use post microinvasive glaucoma surgery is controversial.…”
Section: Lysophosphatidic Acid and Autotaxin In Aqueous Humourmentioning
confidence: 99%
“…136 Trabeculotomy is a procedure which involves cleaving the TM and inner wall of SC to reduce resistance to AH outflow in glaucoma patients. 136 Post-operative corticosteroids are associated with IOP spikes, 137 and therefore their use post microinvasive glaucoma surgery is controversial. Patients who did not receive post-operative corticosteroids demonstrated significantly lower ATX levels in the AH 1 week post-operatively and required significantly less IOP-lowering medications at 3 months versus those who did received steroids.…”
Section: Lysophosphatidic Acid and Autotaxin In Aqueous Humourmentioning
confidence: 99%
See 1 more Smart Citation